Oden Southern Ocean 2010/2011 - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden - Meteorological, oceanographic and ship data collected on board icebreaker Oden during the Oden Southern Ocean 2010/11 expedition - Swedish Polar Research Secretariat (Swedish Polar Research Secretariat, 2018)
The 2010/11 Oden expedition to the Amundsen Sea in Antarctica was the fifth scientific expedition coordinated jointly by the National Science Foundation, the Swedish Polar Research Secretariat, and the Swedish Research Council. This was a two-ship expedition, and a rendezvous with R/V Nathaniel B. Palmer permitted the transfer of equipment and scientists.

The Swedish scientific party on Oden was devoted to studies of oceanography, the biology and chemistry of sea ice and water, the dynamics and evolution of epidemic diseases in seals, and benthic communities. The Swedes on the Palmer team studied the role of bacteria in the carbon cycle, crab predators invading warming Antarctic waters, as well as iodine, iron, and other tracers and their roles in the Amundsen Sea Polynya.

This data set contains meteorological, oceanographic and ship data collected during the American-Swedish expedition Oden Southern Ocean 2010/11, which was an international research cruise using the icebreaker Oden. The expedition embarked from Punta Arenas, Chile on December 8 2010 and arrived in McMurdo Januari 16 2011.Data includes meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure.Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.Ship data: Position, Speed, Course.Further metadata on instrumentation and the individual variables can be found in the info file. Graphics and files describing the route are included in the package.More information on the cruise, links to publications etc. can be found at http://polarforskningsportalen.se/en/antarctica/expeditions/oden-southern-ocean-2010-11

Quality Information:

Obviously erroneous data (e.g. negative air pressure) have been omitted. No other processing or quality check of the data has been undertaken. Users should be aware of this in further data handling and analysis.

Odens expedition till Amundsenhavet i Antarktis 2010/11 var den femte forskningsexpeditionen som samordnades av det amerikanska forskningsrådet National Science Foundation tillsammans med Polarforskningssekretariatet och Vetenskapsrådet i Sverige. Två fartyg ingick i expeditionen och vid ett möte med R/V Nathaniel B. Palmer överfördes utrustning och forskare mellan fartygen.
Det svenska forskningsteamet ombord på Oden undersökte oceanografi, havsisens och vattnets biologi och kemi, dynamik och evolution för epidemiska sälsjukdomar, samt bentiska samhällen. Svenskarna på Palmer undersökte bakteriernas roll för koldioxidsystemet, predatorinvasionen av krabbor i Antarktis allt varmare vatten, samt jod, järn och andra spårämnen och deras roll för Amundsenhavets polynia.

Datamaterialet samlades ombord isbrytaren Oden under expeditionen Oden Southern Ocean 2010/11. Datamaterialet innefattar meteorologiska variabler, oceanografiska variabler, samt position-, fart- och kursdata från fartyget.

Ytterligare metadata om variabler och instrumentation, samt ruttinformation finns i zipfilen.
Oden Southern Ocean 2010/2011 - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden - Meteorological, oceanographic and ship data collected on board icebreaker Oden during the Oden Southern Ocean 2010/11 expedition
Keywords: SURFACE WINDS; AIR TEMPERATURE; HUMIDITY; SURFACE PRESSURE; SALINITY; CONDUCTIVITY; WATER TEMPERATURE; NATURAL ENVIRONMENT; NATUR OCH MILJÖ; Climate Science; Klimatvetenskap; Environmental Sciences; Miljövetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Oceans; Kust och hav